An overview of the groundwater potential in northwest pitas based on subsurface evaluation: a case study of kg. Lok Dangkaan, Pitas, Sabah - Hardianshah Saleh; Baba Musta; Fera Cleophas; Khor, Wei Chung (Faculty of Science & Natural Resources, UMS, 2024)
Kg. Lok Dangkaan is located within the North-West Pitas region. This area is dominated by quaternary alluvium, the Bongaya and the South Bangi Formation, which overlie the Kudat Formation. The Bongaya sediments consist mainly of grey sandstones interbedded with carbonaceous shales, with minor occurrences of conglomerate beds. The sandstones are composed mostly of quartz grains and are cemented by mud matrix. The thickness of the sandstone beds varies from a few centimeters to several meters, and both formations potentially play key roles in the formation of groundwater aquifers. An East-West geoelectrical survey was conducted to evaluate the subsurface and the results indicate three main zones. The topmost layer with thickness of 5-10 meters was interpreted as topsoil and unsaturated zone indicated by resistivity values up to 3800 ohms.m. The second zone was interpreted as a saturated zone, indicated by low resistivity values ranging from 4 to 30 ohm.m and chargeability of 19 msec. This layer corresponds to typical sandstone beds in the Bongaya Formation, which are the most promising zones for an aquifer. The third zone was interpreted as a clay-dominated layer, indicated by low resistivity values of 4-30 ohm.m and high chargeability ranging from 254 to 607 msec. This likely corresponds to a shale-dominated layer within the Bongaya Formation. The preliminary subsurface evaluation suggests the potential for the formation of an unconfined aquifer, with the shale layer acting as an aquifer bed. However, due to the low precipitation in the Kg. Lok Dangkaan area, a detailed study of rock porosity-permeability, rock structural pattern and the recharge of surface-groundwater systems is necessary to support the subsurface evaluation.